Building maintenance achievement in high rise commercial building: a study in Klang Valley, Malaysia - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (Ontario International Development Agency, 2012)
The value of buildings depends on the achievement of the maintenance invested in them. Building maintenance management engages getting maximum benefit from the investment made on the maintenance activities. Building maintenance in high rise commercial buildings in Malaysia is on the increase regardless of size, type, location, and ownership. This paper aims to develop a maintenance achievement index (MAI) to benchmark the performance of building maintenance from a number of key performance indicators (KPIs). Eleven high rise office buildings were investigated through randomly selection in Klang Valley, Malaysia. The research collected 110 respondents from in-house building maintenance personnel and outsourced consultant as well as contractors with managing and operating building maintenance activities experience of high rise commercial buildings through unstructured interviews. In addition, a maintenance achievement equation was formulated from the primary components analysis to generate a multiple score so as to show the level of achievement of building maintenance management. The findings of study had shown that building maintenance practitioners believe quality, safety, time, cost, functionality, and environmental friendliness can be considered as KPIs for building maintenance activities. A single index can also be computed from the maintenance achievement equation to apply different weightings to the respective KPI with different significance such that the performance of building maintenance managements can be compared. The idea of achievement remains unclear among building maintenance practitioners, which makes it complicated to measure whether the performance of a building maintenance management is accomplishment or failure. This research establishes the need to develop a MAI which can be a tool in order to measure and value on the whole performance of the building maintenance activities and compute the success model in a scientific approach in order to ensure the consistency of quality, safety, time, cost, functionality, and environmental